Relative motion of transmembrane segments S0 and S4 during voltage sensor activation in the human BK(Ca) channel - Pantazis, Antonios (The Rockefeller University Press, 2010)
Large-conductance voltage- and Ca(2+)-activated K(+) (BK(Ca)) channel α subunits possess a unique transmembrane helix referred to as S0 at their N terminus, which is absent in other members of the voltage-gated channel superfamily. Recently, S0 was found to pack close to transmembrane segments S3 and S4, which are important components of the BK(Ca) voltage-sensing apparatus. To assess the role of S0 in voltage sensitivity, we optically tracked protein conformational rearrangements from its extracellular flank by site-specific labeling with an environment-sensitive fluorophore, tetramethylrhodamine maleimide (TMRM). The structural transitions resolved from the S0 region exhibited voltage dependence similar to that of charge-bearing transmembrane domains S2 and S4. The molecular determinant of the fluorescence changes was identified in W203 at the extracellular tip of S4: at hyperpolarized potential, W203 quenches the fluorescence of TMRM labeling positions at the N-terminal flank of S0. We provide evidence that upon depolarization, W203 (in S4) moves away from the extracellular region of S0, lifting its quenching effect on TMRM fluorescence. We suggest that S0 acts as a pivot component against which the voltage-sensitive S4 moves upon depolarization to facilitate channel activation.